-10b-45=3(b-15)

Simple and best practice solution for -10b-45=3(b-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10b-45=3(b-15) equation:


Simplifying
-10b + -45 = 3(b + -15)

Reorder the terms:
-45 + -10b = 3(b + -15)

Reorder the terms:
-45 + -10b = 3(-15 + b)
-45 + -10b = (-15 * 3 + b * 3)
-45 + -10b = (-45 + 3b)

Add '45' to each side of the equation.
-45 + 45 + -10b = -45 + 45 + 3b

Combine like terms: -45 + 45 = 0
0 + -10b = -45 + 45 + 3b
-10b = -45 + 45 + 3b

Combine like terms: -45 + 45 = 0
-10b = 0 + 3b
-10b = 3b

Solving
-10b = 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
-10b + -3b = 3b + -3b

Combine like terms: -10b + -3b = -13b
-13b = 3b + -3b

Combine like terms: 3b + -3b = 0
-13b = 0

Divide each side by '-13'.
b = 0

Simplifying
b = 0

See similar equations:

| -4x+6=-2x+5 | | y=-3/5*1+6 | | -84=6(1-9)+4(2+10x) | | 100x?10x=108 | | -1/2+3(y+2)=12 | | -(8x^3+x-3)+(2x^3+x^2)-(4x^2+3x-1)=0 | | 64=64*100 | | 2r^2-11+5=0 | | -4x+6=2x+5 | | 3/2x-1/4=8+4x | | y=3/5*1+6 | | (-12s^2+2s+2)-(7s^2+2)=x | | 2[4+2(5-x)-2x]=x+4 | | 100x?x=15 | | 8+-9-9= | | -2t=8 | | 1/6(2t-8) | | -6+w=-7 | | 38-20=x-7 | | d+3n=one | | 8+g=0 | | 7.2+x=0.6 | | -7/2y-1=5/6y-2/3 | | x^11/9 | | -12+5a+a+11= | | 5p+2=23 | | y^2-z= | | 0=x^2+5x+130 | | k+5=-1 | | 2.6-6.7(7.7x+4.6)=-100.446 | | (3-15y)-(13+8y)= | | x-17=5x+3(1-x) |

Equations solver categories